Upaya Guru Fiqih Dalam Meningkatkan Hasil Belajar Siswa Di Mts Al-Khairaat Falabisahaya - Iskandar Asri (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2022)
Fiqh education is an integral part of religious education, indeed it is not the onlydetermining factor in the formation of the character and personality of students, but has a considerable influence on the character and behavior of students. Fiqh subjects have contributed in motivating students to practice religious values in everyday life. The focus of this research discusses the efforts of educators in increasing students' learning output, especially fiqh subjects, at MTs Al-Khairaat Falabisahaya. To achieve this goal, researchers used a phenomenological-based qualitative approach with a case study research method. The researcher found that the output of this research included the implementation of a one sheet learning plan according to the rules of the Indonesian Ministry of Religion. The application of this research includes indicators of time, teaching materials, learning methods and evaluation. Factors supporting this research are adequate facilities and infrastructure. The inhibiting factor for this research is thebackground of the students, who are not all graduates of madrasas or Islamic boarding schools, so it takes a long time to adapt to deeper religious lessons, namely fiqh lessons.